A facile fabrication of conjugated fluorescent nanoparticles and micro-scale patterned encryption via high resolution inkjet printing. Issue 34 (18th August 2021) - Wang, Min; Jiang, Kunkun; Gao, Yifan; Liu, Yaming; Zhang, Zhenchao; Zhao, Weiwei; Ji, Hongjun; Zheng, Tingting; Feng, Huanhuan
Abstract : We employ a typical micro-emulsion method to fabricate tunable conjugated fluorescent nanoparticles. Those nanoparticles are printed into designed QR patterns. Finally, we achieved ultra-high resolution printing with a resolution of 30 micrometers. Abstract : Conjugated fluorescent materials are getting more and more attention in the biomedical arena due to their high fluorescence intensity, non-bleaching and good biocompatibility. However, conjugated fluorescent materials are still not widely used in the field of anti-counterfeiting and pattern encryption due to their extremely low solubility and enormous difficulties in processing. Here, we use a facile approach to fabricate conjugated polymer fluorescent nanoparticles through a classic micro-emulsion method to address these issues. The particle size, loading materials and fluorescence intensity can be tuned as demanded. Later, these particles are transformed into invisible inks for inkjet printers to achieve micro-scale pattern encryption. These patterns show an ultra-high accuracy of around 30 micrometres. They can be used as QR codes for information encryption with 3 times more information encryption and great anti-counterfeiting ability. Finally, we establish an identification recognition system to check their validity. The scenario is the patient identification system of a hospital. The results show that these tags can be read in less than 3 seconds and they can last for 12 months at least. This facile approach holds great potential and bright prospects in the field of privacy protection, information encryption and anti-counterfeiting.